Starch-based polymer materials as advanced adsorbents for sustainable water treatment: current status, challenges, and future perspectives - Khoo, Pui San; Ilyas, R. A.; Uda, M. N. A.; Abu Hassan, Shukur; Nordin, A. H.; A. S., Norfarhana; Ab Hamid, N. H.; A. Rani, M. S.; Abral, Hairul; Norrrahim, M. N. F.; Knight, V. F.; Lee, Chuan Li; et al. (MDPI, 2023)
Over the past three decades, chemical and biological water contamination has become a major concern, particularly in the industrialized world. Heavy metals, aromatic compounds, and dyes are among the harmful substances that contribute to water pollution, which jeopardies the human health. For this reason, it is of the utmost importance to locate methods for the cleanup of wastewater that are not genuinely effective. Owing to its non-toxicity, biodegradability, and biocompatibility, starch is a naturally occurring polysaccharide that scientists are looking into as a possible environmentally friendly material for sustainable water remediation. Starch could exhibit significant adsorption capabilities towards pollutants with the substitution of amide, amino, carboxyl, and other functional groups for hydroxyl groups. Starch derivatives may effectively remove contaminants such as oil, organic solvents, pesticides, heavy metals, dyes, and pharmaceutical pollutants by employing adsorption techniques at a rate greater than 90%. The maximal adsorption capacities of starch-based adsorbents for oil and organic solvents, pesticides, heavy metal ions, dyes, and pharmaceuticals are 13,000, 66, 2000, 25,000, and 782 mg/g, respectively. Although starch-based adsorbents have demonstrated a promising future for environmental wastewater treatment, additional research is required to optimize the technique before the starch-based adsorbent can be used in large-scale in situ wastewater treatment.